Standardization of Dental Vulnerability Scale scores (EVO-BR) - Daniele Boina de Oliveira; Lorrayne Belotti; Ilana Eshriqui; Flávio Rebustini; Danielle da Costa Palácio; Daiana Bonfim; Marcio Anderson Cardozo Paresque; Danielle Viana Ribeiro; Wander Barbieri; Tamara Kerber Tedesco (BMC, 2024)
Abstract Background Dental Vulnerability Scale (EVO-BR) is an instrument developed to help identifying oral health-vulnerable individuals. This scale comprises 15 items distributed into 4 dimensions. It is the first instrument with the potential to guide clinical and managerial decisions in the oral health field. The aim is to validate a score to enable using EVO-BR in Primary Health Care (PHC). Method The investigated sample included PHC users in five Brazilian regions. Data were collected at two different stages: in 2019 (São Paulo) and in 2022 (Minas Gerais, Mato Grosso, Roraima, Pernambuco e Paraná). Exploratory descriptive study of this scale scores was carried out to create classification ranges. Subsequently, discriminant analysis was performed to assess the accuracy of the established classification. Boosting regression was carried out to check items' weight for the instrument score. Results EVO-BR score ranged from 0 (highest vulnerability) to 15 (lowest vulnerability). Four (4) classification configurations were tested. Score equal to 12 points was the one presenting the best classification of the assessed individuals (100% were correctly classified). Boosting regression has evidenced that items 1 and 2 (Overall health domain) and 14 and 15 (Health Services domain) had the strongest influence on this instrument's score. Conclusion The process to standardize the EVO-BR score and, consequently, to develop assessment ranges, is an important step in the fight against health inequalities, since it provides a tool to help planning actions and interventions aimed at meeting specific needs of the population in the Primary Health Care context.